Early and Rapid Internationalization of Firms from Emerging Economies: Understanding the Heterogeneity of Chinese Exporters. Issue 2 (3rd April 2019) - Tsukanova, Tatyana; Zhang, Xiaotian
Abstract: By synthesizing several theoretical perspectives, we explore the determinants of early and rapid internationalization of firms from China as an example of an emerging economy. Specifically, we examine the symbiosis of foreign knowledge, networks, and government support and their impact on the emergence of born globals (BGs). We use the dataset covering 368 Chinese exporting SMEs. The results provide new insights regarding the nature of their strategic behavior and shed light on the reasons for heterogeneity among exporters.